2019
DOI: 10.1002/jmor.21007
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of femoral cross‐sectional properties in sciuromorph rodents: Influence of body mass and locomotor ecology

Abstract: In several groups of mammals, adaptation to differing functional demands is reflected in long bone cross‐sectional properties (CSP), which relate to the resistance to compression and to bending loads in the craniocaudal and mediolateral directions. Members of the Sciuromorpha (“squirrel‐like” rodents) display a diversity of locomotor ecologies and span three orders of magnitude in terms of body size. The availability of robust phylogenies is rendering them a suitable group to further substantiate the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 79 publications
(162 reference statements)
2
31
0
Order By: Relevance
“…In contrast, the macroevolutionary analyses of bone structure, namely the distribution of bone tissue within a skeletal element (e.g. [6][7][8][9][10]), are comparatively scarce, creating a major impediment to our understanding of vertebrate evolution. Bone structure is known for its high degree of plasticity [11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the macroevolutionary analyses of bone structure, namely the distribution of bone tissue within a skeletal element (e.g. [6][7][8][9][10]), are comparatively scarce, creating a major impediment to our understanding of vertebrate evolution. Bone structure is known for its high degree of plasticity [11].…”
Section: Introductionmentioning
confidence: 99%
“…The arid environment potentially contains harder soils, demanding larger forces during digging that in turn require a stronger stabilization and resistance to forces acting on the femur. However, personal qualitative observations on the smaller datasets used by Mielke et al () and Scheidt et al () indicated that all arboreal and fossorial species share overall a similar range of trait values in their trabecular and cross‐sectional robustness properties, respectively and hence, potentially, the same optima. However, their datasets need to be extended in order to enable an unbiased quantitative comparison with the traits used in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Two previous studies (Mielke et al, ; Scheidt, Wölfer, & Nyakatura, ) analyzed further robustness parameters of the sciuromorph femur (trabecular parameter of the femoral head and cross‐sectional properties along the proximodistal axis, respectively). Mielke et al () found no significant differences between the arboreal and fossorial groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations